Analisis Semiotika Teks pada Arca Loga Lembah Bada - Hermansyah Muttaqin; Sigied Himawan Yudhanto (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
Bada Valley in Central Sulawesi is a megalithic site rich in cultural heritage, one of which is the Loga Statue. This statue holds a historical and symbolic value that is intriguing to analyze through the semiotics of texts to understand its embedded meanings. This study aims to analyze the visual and symbolic signs of the Loga Statue using the semiotic approaches of Peirce and Barthes. The analysis seeks to identify how icons, indices, and symbols on the statue represent the cultural and spiritual aspects of the society that created it. The research employs a qualitative approach with descriptive analysis. Data collection is conducted through direct observation, documentation, and relevant literature studies. The data is then analyzed using semiotic methods to reveal the denotative, connotative, and mythological meanings embedded in the statue. The findings indicate that the Loga Statue possesses symbolic representations related to the animistic-dynamistic beliefs of prehistoric communities. The form and carvings on the statue contain spiritual meanings that reflect the close relationship between humans and the supernatural world. Additionally, the visual patterns on the statue suggest a visual communication system used by past societies to express their cultural values.